Special indications for capecitabine (Xeloda) administration in patients with advanced breast cancer: a case report - Litwiniuk, Maria; Mazur-Roszak, Małgorzata; Bręborowicz, Elżbieta (Contemporary Oncology/Współczesna Onkologia, 2004)
Capecitabine (Xeloda) is a precursor of 5-fluorouracil (5-FU) without cytotoxicity, which is developed after sequential enzymatic transformation to 5-FU. Capecitabine is absorbed from the gastrointestinal tract and is activated during a three-step process in other tissues. Enzymes which activate 5-FU, especially thymidine phosphorylase are more concentrated in tumor than in surrounding tissues. Thus the concentration of the active drug is the highest in the tumor. These are two favorable features of the capecitabine: it is an oral drug with the highest concentration in the tumor cells. The oral administration of capecitabine allows for continuous dose adjustment, which is very important in certain clinical situations e.g. in the presence of bone marrow metastases. We present a case of a 55-year-old female with locally advanced breast cancer. Shortly after induction and consolidation with anthracyclines, anemia and thrombocytopenia occurred. Bone marrow immunochemistry revealed metastases. At the same time bone metastases were also found. In our case report we consider therapeutic possibilities in this case. We have chosen monotherapy with capecitabine, because it is recommended after unsuccessful treatment with anthracyclines and has low myelotoxicity. The oral administration of capecitabine is associated with improved quality of life in patients with advanced breast cancer and is preferred by patients in comparison to iv therapy.